Inside Back Cover: trans‐(Cl)‐[Ru(5, 5′‐diamide‐2, 2′‐bipyridine)(CO)2Cl2]: Synthesis, Structure, and Photocatalytic CO2 Reduction Activity (Chem. Eur. J. 28/2015). Issue 28 (6th July 2015) - Kuramochi, Yusuke; Fukaya, Kyohei; Yoshida, Makoto; Ishida, Hitoshi
<x xml:space="preserve">Abstract</x> trans‐(Cl)‐[Ru(L)(CO)2Cl2]‐type complexes (L: 2, 2′‐bipyridyl derivatives) catalyze CO2 reduction to produce carbon monoxide and formate with a photosensitizer and an electron donor under irradiation of visible light. Amide groups attached to the complexes at the 5, 5′‐positions in the ligand affect the catalytic activities. A systematic study on the photochemical CO2 reduction shows the relationship between the CO2 reduction activities and the reduction potential of the ruthenium complexes. For more details, see the Full Paper by H. Ishida and co‐workers on page 10049 ff.